A comparative analysis of early childhood socioeconomic conditions and educational achievement 15 years later. (December 2020) - Merry, Joseph J; Condron, Dennis J; Torres, Nick
Scholars agree that the early childhood years are highly consequential for later educational outcomes, but we know little about the impact of early childhood socioeconomic conditions at the societal level. This study contributes to the literature by bringing to comparative sociology the proposition that variations in the social structures into which children are born have lasting impacts on their educational outcomes as they progress through secondary education. Drawing on theories of welfare regimes and social stratification, we analyze nation-level data on socioeconomic conditions from the early 2000s via the Organisation for Economic Cooperation and Development and educational performance data from the 2015 Programme for International Student Assessment ( N = 35). In line with our hypotheses, societal inequalities and disadvantages present when children are young are associated with negative achievement outcomes 15 years later and policies that guarantee people basic securities are more consistently associated with positive achievement outcomes than are broad measures of social spending. We conclude by highlighting the value of our approach and suggesting directions for future research on cross-national variations in achievement as a product of socioeconomic conditions during early childhood.